2020
DOI: 10.1080/10409289.2020.1822079
|View full text |Cite
|
Sign up to set email alerts
|

Scotland Embarks on a National Outdoor Play Initiative: Educator Perspectives

Abstract: Research Findings. The Scottish government is in the process of transforming their early childhood learning and care landscape by doubling the number of free hours of childcare for families and by requiring that all children in care spend a significant portion of each day outdoors. Thus, the government is promoting outdoor play programs. We surveyed 45 educators working in 16 outdoor programs and 16 nursery programs in Scotland as this transition was taking place. The survey focused on the benefits, barriers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…Changing new rules-taking indoor to outdoor in Australian and Norwegian context while incorporating outdoor to indoor in Singapore. For Australia, bringing indoor to outdoors is a contrast to the pre-pandemic early years pedagogical context (Howe et al, 2020 ). In relation to the physical environment, reduction of play materials to reduce contact with common play materials were observed across the preschools in Singapore, Australia and Norway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Changing new rules-taking indoor to outdoor in Australian and Norwegian context while incorporating outdoor to indoor in Singapore. For Australia, bringing indoor to outdoors is a contrast to the pre-pandemic early years pedagogical context (Howe et al, 2020 ). In relation to the physical environment, reduction of play materials to reduce contact with common play materials were observed across the preschools in Singapore, Australia and Norway.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers can create effective outdoor learning opportunities for children by providing them time, space, a range of learning materials and experiences (Blanchet-Cohen & Elliot, 2011 ; White, 2011 ). Outdoor play in early years has a long-standing tradition in European and Scandinavian countries and has become part of regular programs in many other countries, including Australia, the UK, New Zealand and Canada (Howe, Perlman, Bergeron and Burn, 2020 ). Studies from Norway and Scotland (Sandseter & Sando, 2016 ; Howe et al, 2020 ) reported that despite the risks and challenges in the outdoor environment, both countries place a higher emphasis on outdoor play for offering a rich learning environment.…”
Section: Early Childhood Education Across the Five Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…By challenging themselves during play, children can manage uncertainties while avoiding excessive risk taking, helping them to develop the skills required to support their increasing autonomy and independence [ 27 ]. Nonetheless, although risky play is supported within the Scottish Government’s resources ( My World Outdoors [ 28 ]), support of this type of play behaviour, and others, varies based on practitioners’ beliefs and understanding of outdoor nature-based play and learning provision [ 29 ]. The authors are not aware of any attempt in the literature to explore play behaviours and risk-taking opportunities among children attending urban ELC settings in Scotland.…”
Section: Introductionmentioning
confidence: 99%